Assessing potential population impact of statin treatment for primary prevention of atherosclerotic cardiovascular diseases in the USA: population-based modelling study. Issue 1 (24th January 2017) - Yang, Quanhe; Zhong, Yuna; Gillespie, Cathleen; Merritt, Robert; Bowman, Barbara; George, Mary G; Flanders, W Dana
Abstract : Objective: New cholesterol treatment guidelines from American College of Cardiology/American Heart Association recommend statin treatment for more of US population to prevent atherosclerotic cardiovascular disease (ASCVD). It is important to assess how new guidelines may affect population-level health. This study assessed the impact of statin use for primary prevention of ASCVD under the new guidelines. Methods: We used data from 2010 US Multiple Cause Mortality, Third National Health and Nutrition Examination Survey (NHANES III) Linked Mortality File (1988–2006, n=8941) and NHANES 2005–2010 (n=3178) participants 40–75 years of age for the present study. Results: Among 33.0 million adults meeting new guidelines for primary prevention of ASCVD, 8.8 million were taking statins; 24.2 million, including 7.7 million with diabetes, are eligible for statin treatment. If all those with diabetes used a statin, 2514 (95% CI 592 to 4142) predicted ASCVD deaths would be prevented annually with 482 (0 to 2239) predicted annual additional cases of myopathy based on randomised clinical trials (RCTs), and 11 801 (9251 to 14 916) using population-based study. Among 16.5 million without diabetes, 5425 (1276 to 8935) ASCVD deaths would be prevented annually with 16 406 (4922 to 26 250) predicted annual additional cases of diabetes and between 1030 (0 to 4791) and 24 302 (19 363 to 30 292) additional cases of myopathy based on RCTs and population-based study. Assuming 80% eligible population take statins with 80% medication adherence, among those without diabetes, the corresponding numbers were 3472 (817 to 5718) deaths, 10 500 (3150 to 16 800) diabetes, 660 (0 to 3066) myopathy (RCTs), and 15 554 (12 392 to 19 387) myopathy (population-based). The estimated total annual cost of statins use ranged from US1.65 to US6.5 billion if 100% of eligible population take statins. Conclusions: This population-based modelling study focused on impact of statin use on ASCVD mortality. Under the new guidelines, if all those eligible for primary prevention of ASCVD take statins, up to 12.6% of annual ASCVD deaths might be prevented, though additional cases of diabetes and myopathy likely occur. Disclaimer: The findings and conclusions in this report are those of the authors and do not necessarily represent the official position of the Centers for Disease Control and Prevention.